Aesthetics versus Ecology: The Complexity of Conserving the Tree Avenue in Pivola - Mirko Silan (Journal for Geography, 2024)
The article addresses the conservation and restoration of the linden tree avenue in Pivola, Slovenia, highlighting the cultural, ecological, and practical challenges associated with managing this type of cultural heritage. Designed as symmetrical, aesthetic features, avenues have acquired historical significance and intrinsic ecological value over the centuries, supporting biodiversity and providing habitats for rare and endangered species. Today they face the challenges from environmental pressures, tree aging, and safety requirements. This article outlines the benefits of a hybrid approach that conserves veteran trees and strategically integrates new planting, taking into account ecological sustainability and historical integrity. In this way, we can ensure that these iconic landscapes remain both a cultural and environmental asset for future generations.